Vietnamese textual methodologies: a comparison of Australian with Swedish and New Zealand early childhood visual literacy contexts. Issue 11 (1st November 2016) - Gilmore, Gwen; Truong, Thi My Dung; Reilly, Michelle
ABSTRACT: For preservice teachers in early childhood education, having a rich exposure to multiple forms of literacy in diverse communities is an essential dimension of their teacher education. In this study, 10 Australian preservice early childhood education students, in the first year of their course, visit two early childhood settings in a large city in Vietnam to make deeper connections between literacy and practice contexts. They photographed literacy events and explored them to deepen their understandings of literacy. This paper examines photographs selected by these student teachers drawing on a framework used by Swedish and New Zealand (NZ) students, which focused on identifying a range of literacy concepts. We found that the Australian students focused on themes, meaning making and visual images for illustrating literacy comparison more frequently than their NZ and Swedish counterparts. Thus, the Mellgreen and Margrain framework has merit for teacher educators in expanding literacies in intercultural contexts.